Bathrocephaly: A Head Shape Associated with a Persistent Mendosal Suture. (January 2013) - Gallagher, Emily R.; Evans, Kelly N.; Hing, Anne V.; Cunningham, Michael L.
Bathrocephaly, a deformity of the posterior skull with bulging of the midportion of the occipital bone, is often associated with a benign variant of the mendosal suture (Mulliken and Le, 2008 ). The endochondral and membranous portions of the occipital bone converge at the mendosal suture, which normally closes during fetal life or early infancy. When it persists, it is associated with a characteristic head shape that requires no intervention. We review the clinical findings associated with postnatal persistence of the mendosal suture and discuss other factors that may be associated with bathrocephaly.